2014
DOI: 10.1371/journal.pgen.1004105
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of eIF4GII by miR-520c-3p Represses Diffuse Large B Cell Lymphoma Development

Abstract: Deregulation of the translational machinery is emerging as a critical contributor to cancer development. The contribution of microRNAs in translational gene control has been established however; the role of microRNAs in disrupting the cap-dependent translation regulation complex has not been previously described. Here, we established that elevated miR-520c-3p represses global translation, cell proliferation and initiates premature senescence in HeLa and DLBCL cells. Moreover, we demonstrate that miR-520c-3p di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 59 publications
2
45
0
Order By: Relevance
“…44 Later studies demonstrated that EIF4G2 is a translational activator in both unstressed cells and tumor cells. 45,46 The aberrant expression of EIF4F components EIF4E and EIF4G has been linked to leukemia progression. [15][16][17] When overexpressed, EIF4G2 mediates an increased protein synthesis rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Later studies demonstrated that EIF4G2 is a translational activator in both unstressed cells and tumor cells. 45,46 The aberrant expression of EIF4F components EIF4E and EIF4G has been linked to leukemia progression. [15][16][17] When overexpressed, EIF4G2 mediates an increased protein synthesis rate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-520-3p was also shown to repress diffuse large B-cell development by targeting EIF4G2 to result in decreased global translation and cell proliferation. 46 As deregulation of mRNA translation has been shown to promote cellular transformation and neoplastic growth, 12,13 targeting translation initiation emerged as a new paradigm for AML therapy and to overcome resistance to anti-BRAF and anti-MEK therapies in melanoma. 18,31 Consequently, drugs disrupting the initiation complex, such as 4EGI, anti-EIF4E antisense oligonucleotides or the antiviral drug ribavirin are currently clinically or preclinically tested.…”
Section: Discussionmentioning
confidence: 99%
“…miR-520c-3p is considered as a negative regulatory factor in the growth of tumors, which presents a low expression in diffuse B cell lymphoma, transcribes initiation factor eIF4GII by targeting regulation and inhibits the formation of cell colonies and the growth of tumors [14] . GPC3 is a transmembrane glycoprotein of cell surface inducing physiological functions such as lymphocytes homing and extracellular matrix adhesion, and its high expression is closely related to tumorigenesis and neoplasm metastasis [15] .…”
Section: Groupmentioning
confidence: 99%
“…A few previous studies reported that microRNA‐520c‐3p (miR‐520c‐3p) plays important roles in several kinds of malignant diseases, including lymphoma , breast cancer , fibrosarcoma , hepatocellular carcinoma (HCC) , colorectal cancer (CRC) , glioma , prostate cancer , and gastric cancer . Of these studies, some indicated that miR‐520c‐3p facilitates tumor growth .…”
Section: Introductionmentioning
confidence: 99%